Practices of heutagogical activities among Malaysia technical university students - Mohamad, Mimi Mohaffyza; Lee, Ming Foong; Masek, Alias; Yee, Mei Heong; Nur Rahma Putra, Andika Bagus (International Journal of Scientific and Technology Research, 2020)
Heutagogical activities aim to produce learner with qualities such as independence, creative, curiosity, resourceful and able to evaluate. It is the needs of learner that will be met along with the lesson. Since this approach provides full autonomy to students in their learning process, the students' readiness needs to be assessed. Thus, this paper aims to identify the dominant heutagogical domains practiced among technical university students. A survey method was used. Data were obtained from 308 randomly selected respondents through a set of questionnaire. the questionnaire was developed beforehand in the previous stage in the research. The data from the survey were analyzed using descriptive statistics. The findings show that the dominant heutagogy domain practiced by the technical university students is Create and the least practiced is the domain of Reflect. This study has an implication on increasing the readiness and application of heutagogy activities among the technical university students.